(untitled) - NIADATUN NIMAH, SITI (LATERNE, 2013)
In the teaching of the German language there are four competence namely listening, speaking, reading, and writing. Writing is an a productive and expressive. Students should be able to master the elements of language such as vocabulary, spelling, coherence between sentences, grammatical. Therefore, to get the maximum learning to write, where the method of teaching is needed. One of them is Example Non-Example. This method is one method of learning can be used to improve learning outcomes in students’ writing competence. Because in this method, the teacher gaves the student material, and then, they get 2 pictures, both match with the themes, and don’t match with the themes. and they are to analyze pictures and suppose to make story into writing. Keywords: writing competence, methods Example Non Example